Selection tools for oil content and fatty acid composition in safflower (Carthamus tinctorius L.) - Cerrotta, Alfonso (2020)
Agricultural expansion requires the deployment of stress-tolerant crops like safflower (Carthamus tinctorius L.). In safflower breeding, oil improvement in early generations requires indirect selection through simply inherited traits. The oil quality is mostly related to the fatty acid profile, which is determined by the OL locus. The aim of this research was to identify simple easy-to-measure traits that indirectly explain oil content varia-tion and its interaction with yield components, and also to generate an effective tool for genotyping the OL locus. A field experiment with F5 and pure lines was carried out to correlate the oil content with 18 traits including yield components, and phenological and morphological characteristics. KASP technology using primers designed according to the ctFAD2-1 gene sequence was applied for OL locus genotyping and vali-dated through fatty acids phenotyping. Hull content, the length:width ratio of the grain, and plant height were identified as the most promising selection tools for increasing oil content, and grains per capitulum was the best yield component for increasing yield without decreasing the oil content. KASP genotyping successfully worked as a MAS tool, identifying oleic and linoleic genotypes. These tools enhance options for improving oil content and quality for safflower breeding.